НАФТОВЕ ЗАБРУДНЕННЯ МОРСЬКИХ ПРИБЕРЕЖНИХ НАНОСІВ - Міронов, О. Г.; Муравйова, I. П.; Гапонюк, Т. О.; Замислова, Т. М. (Marine Ecological Journal, 2023)
The data about quantity content of lipids – hydrocarbon complex in marine deposits of littoral line were received for the first time. The exceeding of quantity of oil hydrocarbons under ones of biogenic origin is observed. It is testify the constant oil pollution of the aquatorium.